PetroChron Antarctica: A Geological Database for Interdisciplinary Use. (16th December 2021) - Sanchez, G.; Halpin, J. A.; Gard, M.; Hasterok, D.; Stål, T.; Raimondo, T.; Peters, S.; Burton‐Johnson, A.
Abstract: We present PetroChron Antarctica, a new relational database including petrological, geochemical and geochronological data sets along with computed rock properties from geological samples across Antarctica. The database contains whole‐rock geochemistry with major/trace element and isotope analyses, geochronology from multiple isotopic systems and minerals for given samples, as well as an internally consistent rock classification based on chemical analysis and derived rock properties (i.e., chemical indices, density, p ‐velocity, and heat production). A broad range of meta‐information such as geographic location, petrology, mineralogy, age statistics and significance are also included and can be used to filter and assess the quality of the data. Currently, the database contains 11, 559 entries representing 10, 056 unique samples with varying amounts of geochemical and geochronological data. The distribution of rock types is dominated by mafic (36%) and felsic (33%) compositions, followed by intermediate (22%) and ultramafic (9%) compositions. Maps of age distribution and isotopic composition highlight major episodes of tectonic and thermal activity that define well known crustal heterogeneities across the continent, with the oldest rocks preserved in East Antarctica and more juvenile lithosphere characterizing West Antarctica. PetroChron Antarctica allows spatial and temporal variations in geology to be explored at the continental scale and integrated with other Earth‐cryosphere‐biosphere‐ocean data sets. As such, it provides a powerful resource ready for diverse applications including plate tectonic reconstructions, geological/geophysical maps, geothermal heat flow models, lithospheric and glacial isostasy, geomorphology, ice sheet reconstructions, biodiversity evolution, and oceanography. Plain Language Summary: On a continent with less than 0.18% of outcrop, information such as the rock type, chemistry and age of Antarctic rock samples are critical inputs for understanding complex interactions between the lithosphere, cryosphere, biosphere, and ocean. We have created PetroChron Antarctica, a relational database containing a compilation of petrological, geochemical and geochronological data from geological samples across Antarctica. The database contains more than 10, 000 samples, along with chemical indices and rock properties calculated from chemical analyses. PetroChron Antarctica contains spatial meta‐information to enable visualization and analysis of the database using an online interactive map, which highlights the variability in crustal geology at the continental scale and can be used for interdisciplinary scientific studies. PetroChron Antarctica is freely available through Zenodo and an ESRI Web Feature Service (http://bit.ly/petrochron ) . Key Points: PetroChron Antarctica is a new relational database containing petrological, geochemical, and geochronological data sets from sampled rocks across Antarctica Lithology and age of geolocated samples, along with computed chemical and physical rock properties, facilitate quantitative analysis and data integration for interdisciplinary use (e.g., geodynamics, oceanography, ice sheet dynamics, biodiversity, and soil studies) The PetroChron Antarctica database is accessible online via a web portal, where data can be freely downloaded as comma‐separated text flat files or individual tables to be used in a relational database system